Private International Law (Conflict of laws) - Garimella, Sai Ramani (Central Law Publication, 2025)
This laudable work by Dr. Sai Ramani Garimella provides a coherent and comprehensive overview of Private International Law. The book makes an ambitious yet modest attempt to draw the attention of the students to more significant works on the subject. Recent developments in India, in the area of civil and commercial laws, addressing cross-border aspects, have been included in this work. The book shall be extremely useful to both undergraduate and postgraduate students, academicians and research scholars having an interest in this branch of law.